2015
DOI: 10.1177/0961203315599449
|View full text |Cite
|
Sign up to set email alerts
|

Chronic active disease pattern predicts early damage in juvenile systemic lupus erythematosus

Abstract: Damage was observed in nearly two-thirds of patients, and occurred earlier in the chronic active pattern. Disease duration, thrombocytopenia and alopecia at onset predicted damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(57 reference statements)
0
11
0
1
Order By: Relevance
“…Persistent active disease itself has been reported to predict early damage in children with lupus. 35 Although the use of corticosteroids has helped improve survival in lupus, the need for prolonged moderate to high doses of corticosteroids especially in children with HDA has resulted in significant cumulative adverse effects contributing to overall long-term damage. Certainly, the general observation worldwide is that these children with lupus survive longer but at the expense of more disease damage and many are corticosteroid related.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent active disease itself has been reported to predict early damage in children with lupus. 35 Although the use of corticosteroids has helped improve survival in lupus, the need for prolonged moderate to high doses of corticosteroids especially in children with HDA has resulted in significant cumulative adverse effects contributing to overall long-term damage. Certainly, the general observation worldwide is that these children with lupus survive longer but at the expense of more disease damage and many are corticosteroid related.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring indices that track treatable disease activity and nonreversible damage have been developed for lupus (57). Single center studies from Canada and Brazil have validated the utility of these activity and damage indices in cSLE patients (58,59), but modifications of the scales developed for adults with SLE have improved overall accuracy (60). Outcomes research in cSLE has also evolved to include health-related quality of life (HRQOL).…”
Section: Tools To Monitor Sle and Advances In Chronic Disease Managementmentioning
confidence: 99%
“…The relationship between disease activity and organ damage showed that, independent from the mean SLEDAI score at disease onset, patients with chronically active disease were at significantly higher risk of developing organ damage; studies by Brunner and Sato showed similar conclusions, confirming that cumulative disease activity is a predictor for organ damage ( 35 , 36 ). To our knowledge, the present study is the longest follow-up study investigating the relationship between disease activity and organ damage in pediatric-onset disease.…”
Section: Discussionmentioning
confidence: 82%